RAPID METHOD FOR QUALITATIVE DETECTION OF MYCOPLASMA PNEUMONIAE. - BHATTACHARJEE MINAKSHI; URHEKAR AD; SHARMA REVATI (International Journal of Pharma and Bio Sciences, 2015)
Mycoplasma pneumoniae is a common etiological agent of atypical pneumonia responsible for 10% to 20% cases. But the organism is not given much attention due to lack of diagnostic facilities. The increased awareness among the health care professionals, timely and rapid detection of the organism could be beneficial. A real time PCR assay adopted in our study can help quicker laboratory diagnosis. The prevalence of Mycoplasma pneumoniae found adopting this method in a tertiary care centre of Navi Mumbai, Maharashtra was 16%.